The General Factor of Personality: The relationship between the Big One and the Dark Triad. (January 2016) - Kowalski, Christopher Marcin; Vernon, Philip A.; Schermer, Julie Aitken
Abstract: The purpose of the present study was to explore the relationship between the General Factor of Personality (GFP) — a personality dimension proposed to be at the top of the personality hierarchy, and the Dark Triad personality dimensions — a cluster of three anti-social personality traits, including: Machiavellianism, psychopathy, and narcissism. A sample of 359 participants completed a measure of the Big 5 personality factors (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism), a Machiavellianism scale, a measure of narcissism, and a measure of psychopathology. The GFP was extracted using a principal axis factor analysis of the Big Five factor scores. The GFP had significant negative correlations with Machiavellianism and psychopathy, but a non-significant correlation with narcissism. A subset of the sample completed a social desirability measure and partial correlations between the GFP and the Dark Triad, controlling for social desirability, were examined. Although the partial correlations were attenuated, the GFP was still significantly and negatively correlated with Machiavellianism and psychopathy and the non-significant correlation with narcissism remained. The results of this study provide further support for the concept of a meaningful pro-social GFP and for the Dark Dyad model (the exclusion of narcissism from the Dark Triad). Highlights: GFP correlated negatively with Machiavellianism and Psychopathy GFP had a non-significant correlation with narcissism All variables correlated significantly with social desirability Inter-scale correlations reduced in magnitude when social desirability was controlled Results support the Dark Dyad model